2019
DOI: 10.1108/apjml-01-2019-0029
|View full text |Cite
|
Sign up to set email alerts
|

The rise of social networking sites

Abstract: Purpose The purpose of this paper is to investigate the impact of the technology acceptance model, privacy concerns and demographic factors on intention to use (ITU) social networking sites (SNSs). Design/methodology/approach A questionnaire survey was developed and administered to a convenience sample of 838 university students. Findings The findings indicate that perceived privacy, demographic factors and perceived usefulness (PU) have a significant effect on the ITU SNSs, and that age does not moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 115 publications
2
16
0
Order By: Relevance
“…To further enhance the users' gratification level, SNS developers should continually modify interfaces and update them frequently with userfriendly tools and attractive layouts. This study's findings revealed that internalization and identification of social influence processes have a significant impact on sustainable intention to use SNS and are congruent with the findings of a number of other researchers (Chiu et al, 2013;Ifinedo, 2016;Li, 2011;Naqvi et al, 2019;Yushi et al, 2018) who reported that internalization and identification improved the sustainable usage of SNS. Our analyses showed that users preferred to use social networking sites that expressed values consistent with their own.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…To further enhance the users' gratification level, SNS developers should continually modify interfaces and update them frequently with userfriendly tools and attractive layouts. This study's findings revealed that internalization and identification of social influence processes have a significant impact on sustainable intention to use SNS and are congruent with the findings of a number of other researchers (Chiu et al, 2013;Ifinedo, 2016;Li, 2011;Naqvi et al, 2019;Yushi et al, 2018) who reported that internalization and identification improved the sustainable usage of SNS. Our analyses showed that users preferred to use social networking sites that expressed values consistent with their own.…”
Section: Discussionsupporting
confidence: 88%
“…The literature (Al-Debie et al, 2013;Lin, 2007) has confirmed that users' positive attitudes towards Instagram had a decided effect on the sustainable intention to use the platform for communication, blogging, e-business opportunities, and entertainment. A substantial body of data supports the idea that the sustainable intention to use SNS explicitly influenced the sustainable pervasive adoption of SNS (Al-Debei et al, 2013;Ifinedo, 2016;Naqvi et al, 2019;Sledgianowski & Kulviwat, 2009;Yushi et al, 2018). Lastly, our results also revealed that attitude not only had a direct positive effect on the intention to use SNS but it also partially mediated the relationship between trust and intention to use SNS (Abduljalil & Zainuddin, 2015).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Second, this study examines the dynamic aspect of consumer attitude toward a company in sequential experimental episodes of NeWOM then of RES, which overcomes the limitations of cross-sectional studies. Also, this current study extends social network theory and the influence of NeWOM on individual perceptions to an online context of consumers in an emerging market in Asia, where studies of NeWOM in online social media networks are relatively scant (Naqvi et al, 2019). More specifically, this study involved a sample of consumers in Thailand, a country where online social media network participation rates are well above the global average.…”
Section: Newom and Firm Crisis Responsementioning
confidence: 75%
“…In recent years, business success has become a competitive task linked with customer experience apart from considering product pricing and differentiation [1]. Integrating eretailing strategies with customer experience can result in significant performance outcomes [2,3]. However, numerous studies have researched online shopping on developing and maintaining an online user experience, still requiring research scholars and online retailers [4,5].…”
Section: Introductionmentioning
confidence: 99%